Les anarchistes espagnols dans les conspirations contre la Dictature et la Monarchie (1923-1930) - Joël Delhom (Cahiers de Civilisation Espagnole Contemporaine)
Between 1923 and 1930, the FAI and the CNT were involved in tactical alliances with the republicans to topple the regime of Miguel Primo de Rivera. In 1931, three FAI militants were sanctioned and the National Committee of the CNT was severely accused. From the unpublished memoirs of Manuel Sirvent Romero (1889-1968), one of the sanctioned members, the 1929-1930 conspiracies and the 1931 congressional debates are presented, with a focus on the collective responsibility of both organizations and the ambiguity of their positions which arose from internal tension.